Use of EDAH Improves Maize Morphological and Mechanical Traits Related to Lodging. (1st March 2019) - Zhang, Qian; Zhang, Lizhen; Chai, Mengzhu; Yang, Deguang; van der Werf, Wopke; Evers, Jochem; Duan, Liusheng
Abstract : Core Ideas: Use of EDAH decreased maize lodging across plant densities. EDAH increased strength, thickness and lignin content of internodes. The use of EDAH lowered ear position and leaf area above the ear. Use of EDAH lowered leaf angle so more leaves were erect. Lodging in maize ( Zea mays L.) is a major constraint to crop yield and quality, especially at high plant densities. A novel growth regulator EDAH, which contains ethephon and diethyl aminoethyl hexanoate (DA‐6), has been recently introduced in maize cultivation in China to alleviate lodging and yield loss. In this study, we aimed to identify how lodging‐relevant morphological and mechanical traits of two maize genotypes respond to EDAH at different plant densities. Two maize hybrids (Zhengdan 958 and Pioneer 335) were compared in treatments with or without EDAH at plant densities of 4.5, 6.0, 7.5 and 9.0 plants m −2 . Lodging percentage was increased at higher plant density in both varieties due to weaker stems and taller plants. The use of EDAH significantly decreased lodging by increasing stem breaking strength, associated with larger stem diameter and higher stem cellulose and lignin contents compared with untreated check. The moment of the wind force on the plant was reduced by the use of EDAH as a result of lower ear positions, more erect leaves, smaller top leaf areas, and shorter internodes. At low plant density, the reduction of lodging by EDAH was mainly due to morphological changes, while at high plant density, the reduction in lodging was mainly due to improved stem breaking strength. We conclude that EDAH reduces lodging risk through the improvement of both morphological and mechanical plant traits and that these effects are expressed across a range of plant densities. The results help to better understand the mechanism of lodging‐yield relationships.